2021
DOI: 10.3390/su13105737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motor-Games-Based Concurrent Training Program on Body Composition Indicators of Chilean Adults with Down Syndrome

Abstract: Background: Concurrent training of strength and endurance has been widely ued in the field of health, with favorable effects on body composition. However, the effect on the body composition of a ludic-motor concurrent proposal in adults with Down syndrome has not been quantified yet. The aim of this study was to determine the effect of a concurrent training program based on motor games on body composition indicators and cardiometabolic risk on schooled male adults with Down syndrome. Methods: The sample is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover, Rimmer et al [22] also found that after 12 weeks of training all outcome measures for cardiovascular fitness, strength, and body composition were improved, whereas the control group in both studies showed almost no change. Moreover, recently, Farías-Valenzuela et al [23] found that 10 months of a concurrent motor games program twice a week improved anthropometric variables in adults with DS. Therefore, although more studies are needed with experimental designs in the adult athlete population with DS, we believe that these results may encourage parents and guardians of individuals with DS to enroll them in some type of sport.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Rimmer et al [22] also found that after 12 weeks of training all outcome measures for cardiovascular fitness, strength, and body composition were improved, whereas the control group in both studies showed almost no change. Moreover, recently, Farías-Valenzuela et al [23] found that 10 months of a concurrent motor games program twice a week improved anthropometric variables in adults with DS. Therefore, although more studies are needed with experimental designs in the adult athlete population with DS, we believe that these results may encourage parents and guardians of individuals with DS to enroll them in some type of sport.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the descrip-tive nature of this study, we do not know if participants who have a lower percentage of fat practice sports or if they have a have a lower percentage of fat because they practice sports. In any case, studies have been carried out on the effect of training in people with DS [2,6,20,22,23,27,28]. For example, it has been seen that in adolescents with DS there was a reduction in the % of body fat after different 12-week training programs [22,27].…”
Section: Anthropometric Variablesmentioning
confidence: 99%
“…In addition, combined exercise programs have shown positive effects on total cholesterol levels, blood pressure, aerobic capacity, and muscle strength [20]. In the same line of work, a 10-month intervention based on structured motor games of strength and endurance showed positive results in adiposity and lean mass levels in a sample of male Down's syndrome patients [39]. The studies selected for the present review have been applied in adults with ID, in which sense Bull et al [40] indicate that adults living with disabilities should perform 150-300 min/wk of moderate-intensity aerobic activity, or 75-150 min/wk of vigorous, functionally oriented, multicomponent strength and balance exercises.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is imperative to control the nutritional state and avoid muscle disuse from school stages in people with ID. Interventions based on the increase in weekly minutes of physical activity from school age could be an alternative for improving muscle strength [ 43 ], as well as structuring training programs through recreational activities to improve the body composition and control of weight in schoolchildren with ID [ 44 ]. It should be noticed that the population under study constantly face a variety of physical, motor, and functional challenges along their lives, and therefore long periods of lockdown or sedentary activities can be highly detrimental to their neuromuscular and cardiometabolic health.…”
Section: Discussionmentioning
confidence: 99%